Laik Fungsi Jalan Provinsi Berdasarkan Peraturan Gubernur Sumatera Utara Nomor 48 Tahun 2023 Tentang Rencana Aksi Keselamatan Lalu Lintas dan Angkutan Jalan Tahun 2024-2028 dan Perspektif Siyasah Dusturiyah - Nasution, Almunadia; Matondang, Maulidya Mora (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the implementation of provincial roadworthiness based on Governor of North Sumatra Regulation No. 48 of 2023 on the Road Traffic and Transport Safety Action Plan 2024–2028, with a particular focus on the Aek Nabara–Ajamu road segment. The research applies a normative legal method with juridical and conceptual approaches, supported by primary legal materials such as laws and regulations, as well as secondary materials including academic literature and the thoughts of classical and contemporary Islamic scholars. The analysis is conducted qualitatively through systematic interpretation and the integration of maqashid al-shari’ah principles, particularly hifzh al-nafs (protection of life) and hifzh al-mal (protection of property). The findings reveal a significant gap between normative law and empirical conditions, as many provincial roads fail to meet roadworthiness standards. From the administrative law perspective, this situation constitutes a violation of legality and accountability principles, while from the siyasah dusturiyah perspective, it reflects negligence in fulfilling leadership responsibilities.